1961
DOI: 10.2136/sssaj1961.03615995002500030029x
|View full text |Cite
|
Sign up to set email alerts
|

Soil Development in Recent Loess in the Matanuska Valley, Alaska

Abstract: Most well-drained soils in the Matanuska Valley, Alaska, are developing in loess which is still being deposited. In deep loess close to the river floodplains that are its source, the soils are Regosols. Farther from the floodplains, in shallower loess, soils are Regosol-Podzol intergrades, and, at still greater distances, they are Podzols. In the Regosols it is likely that the rate of accretion of loess exceeds the rate of horizon differentiation, but that in more distant areas with a lower rate of dust accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
3
5
0
Order By: Relevance
“…6). These observations support those of earlier workers (Rieger and Juve, 1961;Trainer, 1961;Schoephorster, 1968;Clark and Kautz, 1998) that the degree of podzolization in the Matanuska Valley increases to the west. …”
Section: Chemical Weathering In Surface Soils Of Matanuska Valley Loesssupporting
confidence: 90%
“…6). These observations support those of earlier workers (Rieger and Juve, 1961;Trainer, 1961;Schoephorster, 1968;Clark and Kautz, 1998) that the degree of podzolization in the Matanuska Valley increases to the west. …”
Section: Chemical Weathering In Surface Soils Of Matanuska Valley Loesssupporting
confidence: 90%
“…This characteristic is considered to be inherited from the till, which is probably derived from rocks most readily comminuted into fine sand-sized material under glacial crushing and abrasion (Dreimanis and Vagners, 1972). Also of possible relevance to this size distribution is the observation that the 200-60pm fraction coincides with the size range of aeolian material reported from investigations in Norway (Holtedahl, 1953;Klemsdal, 1969;Worsley and Alexander, 1976) and Iceland (Boulton and Dent, 1974), while the 6620pm range is similar to that of wind-blown material in Alaska (Swineford and Frye, 1945;PCwC, 1951;Rieger and Juve, 1961). It is possible, therefore, that some of the fine sand fraction is of an aeolian origin, particularly in the Regosol, where there is a surface maximum of 200-20pm material.…”
Section: Particle Sizesupporting
confidence: 79%
“…Glenn et al (1983) concluded that in glacial times winds were from the north and most likely from katabatic (cold air) winds descending from the greater Yellowstone glacial system. Such an origin of loess via deflation of locally dry outwash plains by katabatic winds probably also produced loess deposits in southern Alaska (Rieger and Juve, 1961) and central Alaska (Thorson and Bender, 1985;Muhs and Budahn, 2006). Loess in Jackson Hole has mineralogy similar to loess found in other regions.…”
Section: Loess In the Jackson Hole Areamentioning
confidence: 95%